Multipurpose Cultural Center - Hadeel makhlouf; Lama Foqha; Malak Salahat; Shahd Hindi (My University, 2016)
The project presents an integrative multi-purpose cultural complex in the western region of Jenin city. From the perspective of the Directorate of Culture in Jenin and the Advisory Council of the district There is lack of cultural facilities for youth, and the large population of governorate which is about 256000 in 2007. That's what encouraged us to choose this proposed project from Jenin District Strategic Development (2008-2017) as graduation project. In addition, we are youth and we feel the urgent need to implement such a project.   The project will be designed in an integrated sustainable manner, which contains architectural, structural, electrical, environmental, mechanical, and safety aspects. Architectural plans that describe the building taking into account the orientation, shape and distribution of the spaces based on the purpose and environmental determinants. In the structural design, the structure will be designed using computer software; the analysis will include 3-D modeling, soil structure interaction, dynamic analysis, and seismic design. The design of elevators, HVAC, installations water and sanitation systems will be carried out through mechanical design. In addition to that, the electrical design includes schematics for lighting, power, acoustical and earthing systems. In the public safety design emergency exits, alarm system, fire protection and fire fighting systems will take a serious manner in line with international codes. Finally, environmental design will appear in all the design steps discussed earlier, in terms of natural lighting and shading, advantages of the Sun heat in summer and winter and rainwater storage. At the end, a comprehensive report showing all design details, drawings and conditions and table of quantities for the buildings will be submitted.

. 256000 2007. (2008-2017) . .    . . . 3-D   . . . . .
Multipurpose Cultural Center